Plasma microRNAs are associated with domain-specific cognitive function in people with HIV. (1st September 2021) - Massanett Aparicio, Julissa; Xu, Yanxun; Li, Yuliang; Colantuoni, Carlo; Dastgheyb, Raha; Williams, Dionna W.; Asahchop, Eugene L.; McMillian, Jacqueline M.; Power, Christopher; Fujiwara, Esther; Gill, M. John; Rubin, Leah H.
Abstract : Objective: Cognitive impairment remains common in people with HIV (PWH) on antiretroviral therapy (ART). The clinical presentation and severity are highly variable in PWH suggesting that the pathophysiological mechanisms of cognitive complications are likely complex and multifactorial. MicroRNA (miRNA) expression changes may be linked to cognition as they are gene regulators involved in immune and stress responses as well as the development, plasticity, and differentiation of neurons. We examined plasma miRNA expression changes in relation to domain-specific and global cognitive function in PWH. Design: Cross-sectional observational study. Methods: Thirty-three PWH receiving care at the Southern Alberta Clinic, Canada completed neuropsychological (NP) testing and blood draw. Plasma miRNA extraction was followed by array hybridization. Random forest analysis was used to identify the top 10 miRNAs upregulated and downregulated in relation to cognition. Results: Few miRNAs were identified across cognitive domains; however, when evident a miRNA was only associated with two or three domains. Notably, miR-127–3p was related to learning/memory and miR-485–5p to motor function, miRNAs previously identified in CSF or plasma in Alzheimer's and Parkinson's, respectively. Using miRNET 2.0, a software-platform for understanding the biological relevance of the miRNA-targets (genes) relating to cognition through a network-based approach, we identified genes involved in signaling, cell cycle, and transcription relating to executive function, learning/memory, and language. Conclusion: Findings support the idea that evaluating miRNA expression (or any molecular measure) in the context of global NP function might exclude miRNAs that could be important contributors to the domain-specific mechanisms leading to the variable neuropsychiatric outcomes seen in PWH. Abstract : Supplemental Digital Content is available in the text